2016
DOI: 10.1175/jas-d-16-0033.1
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Presence of Atmospheric Rivers over the North Pacific during Planetary-Scale Wave Life Cycles and Their Role in Arctic Warming

Abstract: Heretofore, the tropically excited Arctic warming (TEAM) mechanism put forward that localized tropical convection amplifies planetary-scale waves, which transport sensible and latent heat into the Arctic, leading to an enhancement of downward infrared radiation and Arctic surface warming. In this study, an investigation is made into the previously unexplored contribution of the synoptic-scale waves and their attendant atmospheric rivers to the TEAM mechanism. Reanalysis data are used to conduct a suite of obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 77 publications
8
74
0
Order By: Relevance
“…Given the results of the above budget analysis, a natural question to ask is what causes the downward IR to increase. Gong et al () and others showed that the intraseasonal midlatitude winter circulation is an important contributor to the downward IR increase on the same time scale (Baggett et al, ; Doyle et al, ; Lee et al, ; Luo et al, ; Park, Lee, & Feldstein, ; Park, Lee, Son, et al, ; Woods et al, ; Woods & Caballero, ; Yoo et al, , ). Doyle et al () analyzed in situ data in the high Arctic and speculated that increases in warm moist air intrusions into the Arctic could contribute to long‐term warming over the Arctic.…”
Section: Resultsmentioning
confidence: 98%
“…Given the results of the above budget analysis, a natural question to ask is what causes the downward IR to increase. Gong et al () and others showed that the intraseasonal midlatitude winter circulation is an important contributor to the downward IR increase on the same time scale (Baggett et al, ; Doyle et al, ; Lee et al, ; Luo et al, ; Park, Lee, & Feldstein, ; Park, Lee, Son, et al, ; Woods et al, ; Woods & Caballero, ; Yoo et al, , ). Doyle et al () analyzed in situ data in the high Arctic and speculated that increases in warm moist air intrusions into the Arctic could contribute to long‐term warming over the Arctic.…”
Section: Resultsmentioning
confidence: 98%
“…Similarly, Baggett et al. () show how North Pacific planetary‐scale waves with lifetimes of more than 5–7 days strongly modify the synoptic‐scale disturbances and AR moisture fluxes along the high‐latitude North American west coast.…”
Section: Introductionmentioning
confidence: 84%
“…This study seeks to (1) identify observed ARs and examine the latitudinally dependent large‐scale extratropical features—including atmospheric blocking—that precede AR events near the U.S. west coast by more than 1 week during the Northern Hemisphere cool season, (2) assess the ability of an advanced GCM (CESM2) to reproduce the observed AR statistics, and (3) determine whether CESM2 can accurately simulate the observed large‐scale AR “precursor” features. Although previous studies have highlighted large‐scale patterns associated with heavy rain events in the far western United States, most of these rely on limited sample sizes (Ely et al., ; Grotjahn & Faure, ), present dynamical field responses contemporaneous with the AR landfall date (Harris & Carvalho, ; Neiman et al., ) or within 2–4 days prior to landfall (e.g., Lackmann & Gyakum, ; Payne & Magnusdottir, ), investigate AR frequency responses to identified circulation regimes (Amini & Straus, ), or otherwise examine different aspects of the connections between ARs and their antecedent large‐scale patterns in observations, Earth‐like GCMs, or idealized GCMs (e.g., Baggett et al., ; Jiang & Deng, ; Jiang et al., ; Swenson et al., ). This study fills these gaps by investigating the development and time evolution of AR precursor patterns and the role of atmospheric blocking in both an observation‐based data set and within a GCM simulation.…”
Section: Introductionmentioning
confidence: 99%
“…A further avenue for future research is to investigate the regional‐ and planetary‐scale atmospheric and oceanic variability modulating the characteristics of ARs and other atmospheric controls on GrIS SMB. Many recent studies (e.g., Baggett et al, ; Ding et al, ; Flournoy et al, ; Gong et al, ; Jiang et al, ; Yoo et al, ), focusing primarily on Arctic sea ice rather than the GrIS, have detailed the role of tropical forcing in initiating Rossby wave trains that enhance poleward energy and moisture transport to the Arctic. Ding et al () found indications of tropical Pacific forcing of recent negative NAO anomalies and associated warming in northeastern Canada and Greenland, but did not discuss how this forcing modulates synoptic atmospheric phenomena such as ARs, blocking, or Rossby wave breaking in the vicinity of Greenland.…”
Section: Summary and Discussionmentioning
confidence: 99%